50.0k views
0 votes
What is the answer to -2 (6n-5) = 26? PLEASE ANSWER CORRECTLY

User Franssu
by
5.6k points

2 Answers

5 votes

Answer:

n = 1.33 repeating

Explanation:

first you distribute the -2 by everything in the parenthesis so then you get -12 + 1- = 26 the you subtract 10 from each side which leaves you with -12 = 16 then you devide -12 by both sides and you get the decimal 1.33 repeating.

User Sorcy
by
5.4k points
3 votes
This is the answer!! Also I use Photomath to help with my hw!
What is the answer to -2 (6n-5) = 26? PLEASE ANSWER CORRECTLY-example-1
User Majid Soltani
by
4.9k points